2017
DOI: 10.3389/fonc.2017.00047
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for Histological Validation of In Vivo and Ex Vivo Magnetic Resonance Imaging of the Human Prostate

Abstract: This article describes apparatus to aid histological validation of magnetic resonance imaging studies of the human prostate. The apparatus includes a 3D-printed patient-specific mold that facilitates aligned in vivo and ex vivo imaging, in situ tissue fixation, and tissue sectioning with minimal organ deformation. The mold and a dedicated container include MRI-visible landmarks to enable consistent tissue positioning and minimize image registration complexity. The inclusion of high spatial resolution ex vivo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 18 publications
(21 reference statements)
0
47
0
Order By: Relevance
“…On the other hand, strategies based on ExV have only been evaluated in relatively small numbers of prostate specimens, often lack standardization of the experimental design (e.g., to achieve consistent positioning of the specimen with respect to InV), or lack integration into the clinical workflow. Recently, there have been initial investigations of alignment strategies that combine the advantages of patient‐specific molds with ExV, but only proof‐of‐concept results have been reported thus far.…”
mentioning
confidence: 99%
“…On the other hand, strategies based on ExV have only been evaluated in relatively small numbers of prostate specimens, often lack standardization of the experimental design (e.g., to achieve consistent positioning of the specimen with respect to InV), or lack integration into the clinical workflow. Recently, there have been initial investigations of alignment strategies that combine the advantages of patient‐specific molds with ExV, but only proof‐of‐concept results have been reported thus far.…”
mentioning
confidence: 99%
“…As expected, the sensitivity increased with decreasing resolution of MRI datasets to larger voxel size (125.00 mm 3 ). Multiple prior studies evaluated the accuracy of prostate MRI at the ROI level, ranging from 6 ROIs to 30 ROIs, and on the voxel level . In a prior study by Priester et al, tumor extent was underestimated by more than 10 mm in 2/3 of cases, while in Le Nobin et al, underestimation was found to be somewhat smaller, suggesting a 9 mm safety margin in a study where the distance measurement was based on coregistration to histology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multiple research groups have already used 3D‐printed molds and ex vivo imaging to improve registration. Although these methods appear to improve coregistration accuracy, multiple challenges remain . In the IMPROD trial, all prostatectomy specimens were processed identically (Supporting Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations